CHARACTERIZATION AND BIO-ACTIVITY EVALUATION OF PHOSPHOLIPID COMPLEX OF EXTRACT FROM PSIDIUM GUAJAVA LEAVES FOR ANTIOXIDANT & ANTI-INFLAMMATORY ACTIVITY. - TARUN KUMAR DASGUPTA,; PRISCILLA M D’MELLO,; DEEP BHATACHRYA, (International Journal of Pharma and Bio Sciences, 2015)
The polyphenol rich extracts of leaves of P.guajava were evaluated for chemoprofiling and HPLC with respect to standard quercetin. With the HPLC it was calculated that 0.02% quercetin was present in total extracts. After that the complexation with phospholipids was carried out to convert the polyphenols of extracts of leaves of P.guajava into their bio-absorbable lipophilic fraction which improve their pharmacokinetic profile. The activities were evaluated by lipid peroxidation inhibitory activity and anti-inflammatory activity using various in-vitro and in-vivo model. The superiority of the action of complexes has demonstrated the concepts behind the product development of the herbal raw material. In sum the synergism of the bio activity profile of phyto-constituents is possible by their complexation with phospholipids.